Assessing learners' satisfaction towards support services delivery in National Open University Nigeria: implications for counselling services (2013)
This study aims to determining the level of students' satisfaction of learner support services in the study centres of NOUN National Open University of Nigeria and whether the support services offered at the study centres have significant influence on the level of students' satisfaction. A descriptive survey of ex-post facto research design was adopted for this research. Stratified random sampling technique was used in selecting two thousand, one hundred and sixty (2160) samples from eighteen (18) study centres; made up of three (3) study centres in each of the six geopolitical zones of Nigeria. Two hypotheses subjected to Percentile statistics, Friedman Rank Test and Post hoc Wilcoxon Rank Tests via SPSS version 20 at the level of .00 and .01 asymptotic significant level respectively were formulated and analysed in the study The results indicated symbolising significant differences among students' in their satisfaction with learner support services provided by their study centres. Significant difference was also observed on the basis of the geopolitical zones, as learner support services were adjudged to be unsatisfactory in five study centres. Suggestions were offered on how to alleviate the identified problems.